Assessment of Iodine Status among Pregnant Women and Neonates Using Neonatal Thyrotropin (TSH) in Mainland China after the Introduction of New Revised Universal Salt Iodisation (USI) in 2012: A Re-Emergence of Iodine Deficiency?. (7th October 2019) - Zhou, Hang; Ma, Zheng Feei; Lu, Yiming; Pan, Binyu; Shao, Jian; Wang, Liya; Du, Yanyan; Zhao, Qihua
Abstract : Iodine deficiency during pregnancy can cause iodine deficiency disorders (IDD). However, it is unclear about iodine and thyroid status of Chinese pregnant women and neonates after the implementation of the revised universal salt iodisation (USI) level in 2012. Therefore, the aim of the cross-sectional study was to determine iodine nutrition and thyroid status among pregnant women and their neonates in China after the implementation of USI. Medical records of pregnant women and neonates in Northern Jiangsu People's Hospital between January 2016 and December 2017 were reviewed and included. We included 3060 mother-and-newborn pairs in the study. Mean age of participants was 28.2 ± 4.1 years. TSH, FT3, and FT4 of participants were within normal reference range. The overall mean neonatal TSH, birth weight, and prevalence of low birth weight (LBW) were 4.86 ± 2.06 mIU/L, 3358 ± 455 g, and 3.2%, respectively. The prevalence of neonatal TSH values >5 mIU/L was 29.3%, suggesting iodine deficiency in the region. In conclusion, our results indicated iodine deficiency in the region, according to the neonatal TSH cutoff recommended by WHO/UNICEF/IGD. More efforts are urgently required to improve iodine status of pregnant women in the region in order to prevent a re-emergence of iodine deficiency.